An update on the rod microglia variant in experimental and clinical brain injury and disease. Issue 1 (4th January 2021) - Giordano, Katherine R; Denman, Charlotte R; Dubisch, Phoebe S; Akhter, Murtaza; Lifshitz, Jonathan
Abstract: Contemporary microglia morphologies include ramified, activated and amoeboid, with the morphology of microglia considered highly coupled to the cellular function. Rod microglia are an additional activated microglia variant observed in the ageing, injured and diseased brain. Rod microglia were reported frequently in the early 1900s by neuropathologists in post-mortem cases of general paresis, Alzheimer's disease and encephalitis, and then remained largely ignored for almost 100 years. Recent reports have renewed interest in rod microglia, most notably after experimental traumatic brain injury. Rod microglia are formed by the narrowing of the soma and retraction of planar processes, which results in the appearance of an elongated, rod-shaped cell. Rod microglia are most commonly observed in the cortex, aligned perpendicular to the dural surface and adjacent to neuronal processes; in the hippocampus, they are aligned perpendicular to hippocampal layers. Furthermore, rod microglia form trains with one another, apical end to basal end. By replicating the process of sketching microscopic observation, rod microglia are re-defined by circumnutation around the long axis. In this update, we summarize the rod microglia variant in clinical and experimental literature and advocate for investigation into mechanisms of rod microglia origin and function. Abstract : Rod microglia are a variant of activated microglia reported in the brain after neurological injury and disease. Despite their discovery over 100 years ago, little is known about their formation, expression, or function. Advanced molecular tools are required to elucidate the role of rod microglia. Graphical Abstract: